Analysis Of Teacher Self-Efficacy And Competence On Teacher Performance Through Organizational Support For Elementary School Teachers - Ina, Kristina Tamo; Yustiana, Dewi; Nafisah, A’isy Fiklil; Endriatmoko, Yosa; Suminar, Lintang (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the influence of self-efficacy and teacher competence on teacher performance with organizational support as an intervening variable in Elementary School teachers in Loura District, Southwest Sumba Regency, East Nusa Tenggara Province. The background of this study is based on the importance of improving the quality of educational human resources, where self-confidence, professional competence, and school organizational support play an important role in determining the success of teacher performance. The research method used is a quantitative approach with an explanatory research design. The research sample consisted of 45 elementary school teachers determined by proportional random sampling technique. Data collection was carried out through questionnaires that had been tested for validity and reliability. Data analysis used Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of the study indicate that: (1) self-efficacy has a positive and significant effect on teacher performance; (2) teacher competence has a positive and significant effect on teacher performance; (3) self-efficacy has a positive and significant effect on organizational support; (4) teacher competence has a positive and significant effect on organizational support; (5) organizational support has a positive and significant effect on teacher performance; and (6) organizational support has been shown to mediate the influence of teacher self-efficacy and competence on teacher performance. The conclusion of this study is that improving the performance of elementary school teachers in Loura District is not only determined by teacher self-efficacy and competence, but is also greatly influenced by the role of school organizational support. Thus, schools and educational policy makers are expected to pay more attention to teacher empowerment through strengthening self-efficacy, increasing competence, and providing ongoing organizational support.